The valves of the cardiac outflow tract of the starry ray, Raja asterias (Chondrichthyes; Rajiformes): Anatomical, histological and evolutionary aspects. (31st October 2018) - Lorenzale, Miguel; Fernández, Borja; Durán, Ana Carmen; López‐Unzu, Miguel A.; Sans‐Coma, Valentín
Abstract: The cardiac outflow tract of chondrichthyans is composed of the myocardial conus arteriosus, equipped with valves at its luminal side, and the bulbus arteriosus devoid of myocardium. Knowledge of the histomorphology of the conal valves is scarce despite their importance in preventing blood backflow to the heart. Current information on the subject refers to a single shark species. The present report is the first to describe the structure of the conal valves of a batoid species, namely, Raja asterias . Hearts from seven starry rays were examined using scanning electron microscopy and histochemical techniques for light microscopy. In all hearts, the conus showed four transverse rows of three pocket‐like valves each. Each valve was composed of a leaflet and its supporting sinus. The leaflet had a stout central body, rich in glycosaminoglycans, which contained fibroblasts, collagen and elastin. The central body was surrounded by two thin fibrous layers, outer and inner, formed mainly by collagen. The valves of the anterior row, which were the largest of the valvular system, were attached proximally to the conus arteriosus and distally to the bulbus arteriosus, and not to the ventral aorta as previously reported for chondrichthyans. The arrangement of the anterior valves in the starry ray is an anatomical pattern that apparently has been preserved throughout the evolution of vertebrates.